Current status of zirconia implants in dentistry: preclinical tests. Issue 1 (January 2019) - Nishihara, Hironobu; Haro Adanez, Mireia; Att, Wael
Abstract: Purpose: This systematic review aimed to provide an overview of zirconia implants as well as regarding the outcome of the implant-restorative complex in preclinical studies. Study selection: An electronic search of the literature prior to July 2017 was performed to identify all articles related to preclinical research on zirconia implants. The search was conducted using MEDLINE (National Library of Medicine) and PubMed without restrictions concerning the date of publication. The search terminology included: zirconia implant, osseointegration, bone-to-implant contact, soft tissue, histology, histomorphometry, surface modification, surface roughness, surface characteristics, and restoration (connecting multiple keywords with AND, OR). Results: Fifty-seven studies were finally selected from an initial yield of 654 titles, and the data were extracted. The identified preclinical studies focused on several aspects related to zirconia implants, namely biocompatibility, mechanical properties, implant design, osseointegration capacity, soft tissue response, and restorative options. Due to heterogeneity of the studies, a meta-analysis was not possible. The most frequently used zirconia material for the fabrication of implants is yttria-stabilized tetragonal zirconia polycrystal. The resistance-to-fracture for zirconia implants ranged between 516–2044 N. The mostly investigated parameter was osseointegration, which is compared to that of titanium. A lack of evidence was found with other parameters. Conclusions: Due to its good biocompatibility as well as favorable physical and mechanical properties, zirconia implants are a potential alternative to titanium implants. However, knowledge regarding the implant-restorative complex and related aspects is still immature to recommend its application for daily practice.